Effect of travel speed ​​and arc length on geometry and heat accumulation in WAAM-GMAW process - Agus Sifa; Ario Sunar Baskoro; Afrizal Riyantono; Faza Khoirina; Gandjar Kiswanto; Syarif Junaidi (Prosiding SNTTM, 2025)
Wire arc Additive Manufacturing (WAAM) is a technology capable of manufacturing large and complex components using aluminum alloys. This is due to its high deposition rate and efficient material utilization. However, WAAM faces several issues, particularly regarding process stability. In the WAAM process, especially when using Gas Metal Arc Welding (GMAW), stability is largely determined by controllable process parameters such as travel speed and arc length. This study aims to clarify how fusion stability, influenced by travel speed and arc length, affects the resulting deposit geometry and heat accumulation. The experimental method involved conducting a single-layer WAAM process using GMAW, with ER5356 filler (diameter 1 mm) and AA6061 substrate. During the single-layer WAAM GMAW process, the heat temperature and current were measured in real-time on the deposits. The results included minimum and maximum height and width measurements of the deposits produced. It was observed that increasing the travel speed reduced the current, thereby lowering the heat input. Heat accumulation, under fixed parameters of 80 A current, 16 V voltage, and varying travel speeds and arc lengths, fluctuated throughout the process. At an arc length of 6 mm, the single-layer deposit geometry exhibited humping, causing irregular widths and heights. Overall, both travel speed and arc length played significant roles in determining the maximum and minimum heights of the deposits.